Dayah Is an Islamic Educational Institution for the Acehnese Community - Rifqi, Ahsanur; Dehham, Sabeeha Hamza (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
This article aims to analyze Dayah as an Islamic educational institution in Aceh. This research uses qualitative methods with the type of library study. The research results found that Dayah, as the oldest Islamic educational institution in Southeast Asia, has a long history, unique Islamic education system, and characteristics and has played an important role in the order of life from the time of the Islamic kingdoms until now. Through a deeper understanding of Dayah, we can appreciate the important role this institution plays in maintaining the community’s religious identity.